1921 N.M. Laws 57-58 - (:unkn) unknown (My University, 1921)
Ch. 35, § 16: No game shall be pursued, taken, wounded or killed in the night, or with a steel or hard pointed bullet or with any weapon other than an ordinary shoulder gun or pistol, and the use of high powered rifles in hunting and taking migratory game birds is hereby prohibited.
Keywords: HUNTING REGULATION